THE EFFECTIVENESS OF DISCOVERY LEARNING AND PROBLEM SOLVING LEARNING MODEL ON MATHEMATICAL PROBLEM SOLVING SKILLS OF CLASS IV PRIMARY SCHOOL - Yuniarti Kusumaningrum; Endang Indarini (Laboratorium Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Riau, 2020)
This research conducted with the aim to determine differences in the effectiveness of the model of Discovery Learning and Problem Solving of problem-solving ability mathematics students of class IV primary school. The type of the research is quasi-experimental with the use of test prerequisites that consist of normality test and homogeneity. In this study, prerequisite test was conducted to determine normality and homogeinity. From the T test using Independent Samples Test showed t count > t table with value 7,113 > 2,007 with significance 0,000 < 0,05 that means Ho is rejected and Ha accepted. Based on the results obtained there are differences in the effectiveness of significant. The results of the test N-Gain there is an increase after the treatment is given in the experimental class using the model of Discovery Learning by 0.40 and the control class there is an increase after a given model Problem Solving of 0.16. Based on these results, it showed that the model of Discovery Learning is more effective when compared with the Problem Solving model to increase problem solving ability in mathematics of students of class IV primary school.